Socio-economic differentiation of society: statistical trends - M.V. Ivanova; A.V. Ivanov (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
The purpose of the research was to study the statistical trends of social inequality in Ukrainian society. There are a lot of modern studies devoted to the methodology for quantifying this problem, but almost all of them concern the identification and study of the middle class. In Ukrainian society such a formulation of the problem seems to be debatable due to the small number of these social groups. Therefore, the attention of the authors was focused on the study of facts and dynamics in the distribution of the income of society. For this purpose, official statistical information was used: intervals of distribution of citizens by the level of total income. It is shown that these data do not allow to correctly establishing the pattern of changes in social inequality in long-term dynamics, for example, in the period 2012-2020. Also, for these purposes, it is problematic to use the «Gini’s coefficient», since its quantitative values are quite dependent on the boundary values of the extreme intervals of the income distribution series. And they give a controversially dubious result. The study of issues of social inequality is also complicated by the fact of the existence of illegal economic activity in Ukraine and officially unaccounted income of citizens. To solve the problem, we have built a graphical profile of socio-economic differentiation, as the dependence of the number of the «і-th» income group of society not on the amount of income, but on the number of the corresponding ranked interval. Revealing the middle interval (or decile group) makes it easy to identify the asymmetry in the distribution of income. We see the advantage of this approach to the analysis of the set task in two aspects: in the possibility of a reliable and objective assessment of the dynamics of social stratification, and in a simpler method of calculation and visualization. The revealed regularity of increasing asymmetry in the distribution of incomes of society in 2020 confirmed by the calculated values of the asymmetry coefficients: Аsµ(2012)=0.95 and Аsµ(2020)=1.20. So, in the science work substantiates an increase in socio-economic differentiation and inequality in 2020 relative to the pre-crisis period of 2012. It is expected that the revealed statistical trend of increasing social inequality can be affect in the aggravation of socio-economic and political problems in society.